Gut microbiome in chronic rheumatic and inflammatory bowel diseases: Similarities and differences. Issue 8 (1st October 2019) - Salem, Fatouma; Kindt, Nadège; Marchesi, Julian R; Netter, Patrick; Lopez, Anthony; Kokten, Tunay; Danese, Silvio; Jouzeau, Jean-Yves; Peyrin-Biroulet, Laurent; Moulin, David
Abstract : Introduction: Inflammatory bowel diseases (IBDs) and chronic rheumatic diseases (CRDs) are systemic chronic disorders sharing common genetic, immune and environmental factors. About half of patients with IBD develop rheumatic ailments and microscopic intestinal inflammation is present in up to half of CRD patients. IBD and CRD patients also share a common therapeutic armamentarium. Disequilibrium in the complex realm of microbes (known as dysbiosis) that closely interact with the gut mucosal immune system has been associated with both IBD and CRD (spondyloarthritis and rheumatoid arthritis). Whether dysbiosis represents an epiphenomenon or a prodromal feature remains to be determined. Methods: In an attempt to further investigate whether specific gut dysbiosis may be the missing link between IBD and CRD in patients developing both diseases, we performed here a systematic literature review focusing on studies looking at bacterial microbiota in CRD and/or IBD patients. Results: We included 80 studies, with a total of 3799 IBD patients without arthritis, 1084 CRD patients without IBD, 132 IBD patients with arthropathy manifestations and 12 spondyloarthritis patients with IBD history. Overall, this systematic review indicates that an increase in Bifidobacterium, Staphylococcu s, Enterococcus, Lactobacillus, Pseudomonas, Klebsiella and Proteus genera, as well as a decrease in Faecalibacterium, Roseburia genera and species belonging to Verrucomicrobia and Fusobacteria phyla are common features in IBD and CRD patients, whereas dozens of bacterial species are specific features of CRD and IBD. Conclusion: Further work is needed to understand the functions of bacteria and of their metabolites but also to characterize fungi and viruses that are commonly found in these patients.